TINGKATAN RAGAM BAHASA IBU RUMAH TANGGA DAN IBU KARIR DI DAERAH RUMBAI JALAN KARTIKA SARI KAJIAN SOSIOLINGUISTIK - Evizariza, Evizariza; Yani, Juli; Rismayeti, Rismayeti (EDUTECH CONSULTANT, 2017)
Language diversity is not only show their social differences in society, but also an indication of the situation-speaking members that reflect the objectives, topics, rules and the mode user mode language. Variety Indonesian used by people who live in the neighborhood terminal will of course be different from the kind of language the people who live in a residential neighborhood, a variety of language teachers must be different with a variety of languages merchant, or a variety of language public figures will vary with variety of language ordinary people , as well as language diversity of people who have a low level of the economy generally different regional variations of rich people.